Bilateral nevus of Ota: A case series and literature review - Pinki Kumari; Vartika; Pallavi UK; Rajesh Sinha (Asian Journal of Medical Sciences, 2023)
Nevus of Ota is a dermal melanocytic hamartoma clinically characterized by confluence of blue-to-gray macules, distributed along the ophthalmic and the maxillary divisions of the trigeminal nerve. It is usually unilateral and only 5–15% of cases have been reported to have bilateral involvement. This entity has been reported predominantly in darkly pigmented individuals, particularly in Asians and blacks. Case reports and case series describing this unique entity are very rare in literature. Herein, we report three cases of bilateral nevus of Ota at a tertiary care center in Eastern India. A detailed history, clinical examination, Wood’s lamp examination, and histopathological correlation were done in all the cases. In all the cases, lesions started with bluish pigmentation on the sclera and out of three cases, two had palatal involvement as well.